Strengthening mechanism and corrosion behavior of friction stir welded LAZ933 magnesium-lithium alloy - Shikang Gao; Hongyun Zhao; Gaohui Li; Guangda Sun; Li Zhou; Yaobang Zhao (Journal of Magnesium and Alloys, 2024)
In this study, friction stir welding (FSW) technique was applied to the LAZ933 magnesium-lithium (Mg-Li) alloy. Microstructure, mechanical properties and corrosion behaviors of friction stir welded LAZ933 magnesium-lithium alloy were analyzed by optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffractometry (XRD), transmission electron microscopy (TEM), hardness, tensile, and electrochemical test. The experimental results indicated that FSW resulted in significant refinement of β phase, reduction of α phase content as well as dissolution of Mg17Al12 and AlLi (γ) precipitates in the nugget zone (NZ). The generated MgLi2Al (θ) precipitates in the NZ and heat-affected zone (HAZ) which had a coherent structure with the matrix could significantly strengthen the Mg-Li alloy. The ultimate tensile strength of the joint reached 163.5 MPa, and elongation reached 15.21%. In the weakest area of the weld (HAZ), the strengthening caused by the solid solution of α phases and formation of θ precipitates compensated the strength loss induced by the phase coarsening by thermal exposure in FSW, resulting in the joint fractured in the base metal (BM) and showed a ductile pattern. The corrosion current density changed from 4.831 × 10−5 A/cm2 to 2.054 × 10−5 A/cm2, which indicated that the weld had better corrosion resistance than the BM.